Human Non-Pigmented Ciliary Epithelium Bradykinin B2-Receptors: Receptor Localization, Pharmacological Characterization of Intracellular Ca2+ Mobilization, and Prostaglandin Secretion. (April 2014) - Sharif, Najam A.; Wang, Yu; Katoli, Parvaneh; Xu, Shouxi; Kelly, Curtis R.; Li, Linya
Abstract Purpose: To characterize the bradykinin (BK) receptor system in human non-pigmented ciliary epithelium (NPCE) using immunohistochemistry and functional cell-based techniques. Methods: B2-receptor protein expression was studied in sections of human donor eyes and in Cynomolgus monkey eyes using immunohistochemical methods. The pharmacological characteristics of intracellular Ca2+ ([Ca2+]i) mobilization in response to BK and related peptides, and blockade by two antagonists, was studied in primary human (p-h-NPCE) and in immortalized human NPCE (imh-NPCE) cells. Prostaglandins (PGs) release induced by BK was also studied in both cell-types using ELISA assays. Limited studies on primary human ciliary muscle (h-CM) cells and human trabecular meshwork (h-TM) cells and Chinese hamster ovary cells expressing human cloned B2-receptors (CHO-B2) were performed to compare with responses in both the NPCE cell-types. Results: B2-receptor immunoreactivity was observed on human and Cynomolgus monkey NPCE cells on eye sections from both species. BK and related analog peptides differentially activated signaling mechanisms in NPCE cells by mobilizing [Ca2+]i, and the BK-evoked responses were blocked by B2-receptor-selective antagonists, HOE-140 and (S)-WIN-64338. Relative agonist potencies (EC50, nM) in p-h-NPCE cells [and in imh-NPCE cells] were: BK = 3.4 ± 0.4 [6.3 nM]; Hyp3-BK EC50 = 1.7 ± 0.2 [6.0 nM], Lys-BK EC50 = 7.0 ± 0.3 [19.8 nM]; Met-Lys-BK EC50 = 106 ± 57.8 [125 nM]; Des-Arg9-BK EC50 = >10, 000 [16 µM]. The antagonist potencies for attenuating BK-induced mobilization of [Ca2+]i in these cells were: HOE-140 (Ki = 7.9 ± 1.8 nM, n = 4) and (S)-WIN-64338 (Ki = 451 ± 44 nM, n = 4). These NPCE cell data correlated well with those obtained for h-CM and h-TM cells, and with B2-receptor binding (r = 0.99, p < 0.0001). However, BK failed to stimulate total PGs production in both NPCE cell-types even though 10% bovine serum increased PG release (by 4.9-fold above baseline), and even though BK stimulated PG release from h-CM, h-TM and in CHO-B2 cells. BK (1 µM) also failed to increase nitric oxide (NO) levels in NPCE cells even though sodium nitropruside increased NO production by 3-fold. Conclusions: Human and monkey NPCE express immunoreactive B2-receptor proteins. These proteins were functionally active, since BK and related peptides potently stimulated mobilization of [Ca2+]i in p-h-NPCE and imNPCE cells that was blocked by two B2-selective antagonists. Down-stream signaling from B2-receptor activation did not appear to involve PG synthesis/release (or NO production) in NPCE cell-types under the present conditions, even though h-CM, h-TM and CHO-B2 cells exhibited robust PG synthesis and release in response to BK.